True double aortic lumen in tetralogy of Fallot. - Marinho da Silva, A (1998)
In an infant with tetralogy of Fallot submitted to angiographic study, a double aortic lumen was found. Although no particular complaints were related to the additional abnormality, we report this case to emphasize the possibility of occurrence of persistent embryonic fifth aortic arch.